The Effectiveness of The Kangaroo Mother Care for Low Birth Weight Baby in Maintaining Thermoregulation Stabilization: a Case Study - Anggeriyane, Esme; Noorhasanah, Evy; Nurhayati, Indah (Universitas Pendidikan Indonesia, 2021)
Introduction: Low Birth Weight (LBW) is the condition when a baby is born weighing less than 2,500 grams. LBW is one of the public health problems that get special attention because effected short and long-term problems. One of the problems is the infant's thermoregulation, such as hypothermia which can cause death. The intervention that can be done is Kangaroo Mother Care (KMC) that chosen because able to increase temperature through a heat transfer and enhance parent-baby bonding. Objectives: the study aimed to analyze the KMC of low birth weight babies in maintaining thermoregulation stabilization. Method: The research used an evaluative design is a case study with data analysis using descriptive-analytic. Results: The case study was conducted on one baby born at 32 weeks' gestation spontaneously and birth weight 1420 gr. The client has a risk of hypothermia, so the kangaroo method is treated for three days. Discussion: Evaluation from 3 days of implementation is the increase in body temperature before and after the KMC for 1st day was 36.4o C to 36.9o C, on 2nd day was 36.6o C to 36.8o C, on 3rd day was 36.8o C to 37.1o C. The KMC is recommended for increasing the baby's body temperature, so it is hoped this method can be carried out by health workers and the baby's parents.ABSTRAKLatar belakang: Berat Badan Lahir Rendah (BBLR) adalah kondisi bayi lahir dengan berat badan kurang dari 2.500 gram. BBLR merupakan salah satu masalah kesehatan masyarakat yang mendapat perhatian khusus karena menimbulkan masalah jangka pendek dan jangka panjang. Salah satunya adalah masalah termoregulasi bayi seperti hipotermia yang dapat menyebabkan kematian bayi. Intervensi yang dapat dilakukan adalah Kangaroo Mother Care (KMC) yang dipilih karena mampu meningkatkan suhu melalui perpindahan panas dan meningkatkan bonding orang tua-bayi. Metode: Penelitian ini menggunakan rancangan evaluative dalam bentuk studi kasus dengan analisa data menggunakan deskriptif analitik. Hasil: Studi kasus yang dilakukan pada seorang bayi yang lahir pada usia kehamilan 32 minggu secara spontan dan berat lahir 1420 gr. Klien memiliki resiko hipotermia sehingga dilakukan perawatan metode kanguru selama 3 hari. Diskusi: Evaluasi dari 3 hari implementasi, peningkatan suhu tubuh sebelum dan sesudah tindakan KMC pada hari 1 ialah 36,4o C menjadi 36,9o C, pada hari 2 ialah 36,6o C menjadi 36,8o C, pada hari 3 ialah 36,8o C menjadi 37,1o C. Berdasarkan data tersebut perawatan metode kanguru direkomendasikan untuk meningkatkan suhu tubuh bayi, sehingga diharapakan metode ini bisa dilakukan oleh tenaga kesehatan dan orang tua bayi.